2011
DOI: 10.1159/000331457
|View full text |Cite
|
Sign up to set email alerts
|

Cheyne-Stokes Respiration in Patients with Heart Failure: Prevalence, Causes, Consequences and Treatments

Abstract: Cheyne-Stokes respiration (CSR) is characterized by a pattern of cyclic oscillations of tidal volume and respiratory rate with periods of hyperpnea alternating with hypopnea or apnea in patients with heart failure. CSR harms the failing heart through intermittent hypoxia brought about by apnea and hypopnea and recurrent sympathetic surges. CSR impairs the quality of life and increases cardiac mortality in patients with heart failure. Thus, CSR should actively be pursued in patients with severe heart failure. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 209 publications
(157 reference statements)
4
18
0
5
Order By: Relevance
“…Alternatively, the Cheyne-Stokes respiration may be a consequence of heart failure in the context of FD as this was shown in non-Fabry patients [48] …”
Section: Sleep-related Breathing Disorder and Muscular Involvementmentioning
confidence: 93%
“…Alternatively, the Cheyne-Stokes respiration may be a consequence of heart failure in the context of FD as this was shown in non-Fabry patients [48] …”
Section: Sleep-related Breathing Disorder and Muscular Involvementmentioning
confidence: 93%
“…Previous studies have shown that over a third of patients with right heart failure due to pPH suffer from Cheyne-Stokes respiration/central sleep apnea [15,16], similar to patients with left ventricular heart failure. In left heart failure, noninvasive positive pressure ventilation or oxygen might be effective therapies as adjuncts to drug treatment [17]; however, studies in pPH are lacking. Other reasons for reduced nocturnal oxygen saturation (Sp o 2 ) might be an increased ventilation perfusion mismatch and impairment of respiratory muscle efficiency due to the recumbent position.…”
Section: Introductionmentioning
confidence: 99%
“…Even though this link between SDB and diastolic dysfunction is evident, the underlying pathophysiological mechanisms are still not well characterized. It has been hypothesized that both elevations in nocturnal BP and activation of the sympathetic nervous system might contribute to this effect [29,30,31] by increasing LV afterload [32]. Furthermore, futile inspiratory efforts hallmarking obstructive sleep apnea might increase LV transmural pressure and hence afterload by inducing negative intrathoracic pressures [32], ultimately provoking diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%